Ammonium‐assisted green fabrication of graphene/natural rubber latex composite. Issue 1 (6th December 2012) - Li, Chengpeng; Feng, Chunfang; Peng, Zheng; Gong, Wei; Kong, Lingxue
Abstract: Direct incorporation of nano reinforcement fillers has been a challenge for composite design because of strong aggregation. In this article, a stabilizer‐free method is developed to prepare new graphene/natural rubber latex (NRL) composite as the stabilizer ammonium was diffused completely in the final heat vulcanization. The as‐prepared composite was investigated by scanning electron microscopy, static mechanical analysis, dynamic thermal mechanical analysis, swelling analysis, and positron annihilation analysis. The results demonstrated that because of good dispersion and special two‐dimensional structure of the graphene, there is strong interfacial interaction originated from the π–π interactions and hydrogen bonds between graphene and NRL matrix even at a low loading. After the introduction of graphene, the glass transition temperature ( T g ) and the crosslink density are improved to 6°C and 7%, respectively, with a slight decrease in overall free‐volume number (3.5%) and fraction (1%). It is also surprising to notice that the tensile strength of NRL is improved to 8% without compromising the elongation at break, which actually increases 3%. Therefore, ammonium‐assisted dispersion of graphene is feasible for graphene/NRL fabrication. POLYM. COMPOS., 2013. © 2012 Society of Plastics Engineers